es 2012
DOI: 10.20955/es.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Easing the Swedish Way

Abstract: (Anderson, Gascon, and Liu, 2010).Generally speaking, QE programs seek to (i) increase asset prices throughout the economy and (ii) reinforce "forward guidance"-that is, policymakers' commitment to sustain the policy rate at an unusually low level for a significant period (Eggertsson and Woodford, 2003). Most central banks tend to implement QE through large-scale purchases of government securities or similar assets. The Riksbank's executive board considered but decided against purchasing assets, in part becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The first loans were granted in October 2008, and after that loans were offered regularly until the end of October 2010 (Elmér et al ). The Riksbank's unconventional monetary policy measures also included offering loans to counterparties in U.S. dollars and approving a wider range of securities as collateral (Andersen ; Elmér et al ; Ingves ). Asset purchase programs were not used before 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The first loans were granted in October 2008, and after that loans were offered regularly until the end of October 2010 (Elmér et al ). The Riksbank's unconventional monetary policy measures also included offering loans to counterparties in U.S. dollars and approving a wider range of securities as collateral (Andersen ; Elmér et al ; Ingves ). Asset purchase programs were not used before 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In April 2009, the Riksbank reduced the policy rate to 0.5% and indicated that 'the repo rate is expected to remain at a low level until the beginning of 2011'; in July 2009, the Riksbank reduced the policy rate to 0.25%, and changed its explicit policy rate guidance to that 'the repo rate is expected to remain at this low level until autumn 2010'. 2 1 See http://www.riksbank.se/en/Interest-and-exchange-rates/Repo-rate-table/. The Executive Board's decision to cut the repo rate to 0.25% was announced on 2 July 2009, and its decision to increase the repo rate to 0.5% was announced on 1 July 2010.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in the repo rate became e¤ective on 8 July 2009 and 7 July 2010, respectively. 2 An overview of these repo announcements is available at: http://www.riksbank.se/en/Monetary-Recently, Williams (2012, 2013) proposed a novel way to investigate the e¤ectiveness of monetary policy when policy rates are (close to) zero. They estimate the time-varying sensitivity of yields to macroeconomic announcements using high-frequency data and compare that sensitivity to a benchmark period in which the ZLB was not a concern.…”
Section: Introductionmentioning
confidence: 99%